VD_FINDINFO HC / 2025 / 720 vom 25. September 2025 - VD Tribunal cantonal (2025)
AUTORISATION DE PROCÉDER, PARTIE À LA PROCÉDURE, DÉCISION D'IRRECEVABILITÉ | 308 al. 1 let. a CPC (CH), 312 al. 1 CPC (CH)